Determination of Cefoperazone Sodium in Pharmaceutical Formulations by Fe3+-Phenanthroline Spectrophotometry - Sha, Ou; Liao, Yin; Zhou, Yun; Liang Zhang, Si; Ma, Weixing (Asian Journal of Chemistry, 2013)
A new method for determination cefoperazone by spectrophotometry was developed based on Fe3+ as the oxidizer of cefoperazone and phenanthroline as the colouring reagent of Fe2+, which was produced from Fe3+. Under the optimum conditions, the relationship between the absorbance and the concentration of cefoperazone was linear in the range of 0.50-12.50 mg/L, the regression equation was A = 0.1179 c (c: mg/L) +0.0003, the relative coefficient was 0.9985. The proposed methods have been applied to the determination of cefoperazone content in pharmaceutical formulations with satisfactory results.